2020
DOI: 10.36351/pjo.v36i4.1086
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Conventional Trabeculectomy in Terms of Intraocular Pressure and Visual Acuity in Primary Open Angle Glaucoma

Abstract: Purpose:  To determine the outcomes of conventional trabeculectomy in terms of decrease in Intra Ocular Pressure (IOP) and improvement in visual acuity in patients of primary open glaucoma, coming to a tertiary care hospital. Study Design:  Retrospective case series. Place and Duration of Study:  Ophthalmology department of a tertiary care hospital from January 2017 to December 2018. Methods:  Patients undergoing trabeculectomy for Primary open angle glaucoma were included. Patients with repe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…On the other hand, there was no statistically significant change in visual acuity of our patients which is in line with other studies reported. 4,9,11 The mean decrease in IOP noted in our study was similar to the results of a study conducted by Shahid et al 4 Similarly, a study conducted in Nigeria also reported a significant reduction in IOP. 12 Even though a higher IOP reduction was reported in our study, setting a target pressure is always individualized according to the patient individual characteristics.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…On the other hand, there was no statistically significant change in visual acuity of our patients which is in line with other studies reported. 4,9,11 The mean decrease in IOP noted in our study was similar to the results of a study conducted by Shahid et al 4 Similarly, a study conducted in Nigeria also reported a significant reduction in IOP. 12 Even though a higher IOP reduction was reported in our study, setting a target pressure is always individualized according to the patient individual characteristics.…”
Section: Discussionsupporting
confidence: 91%
“…3 Pakistan has a burden of over 1.8 million people suffering from glaucoma with more and more people becoming blind to this disease due to delayed presentation primarily due to lack of knowledge. 4 Control of intraocular pressure (IOP) can be achieved with IOP-lowering topical medications, OPEN ACCESS lasers, or surgery. Trabeculectomy, a filtration surgery, first introduced by Cairns in 1968 and then modified subsequently by Watson in 1970, has been the Gold Standard surgical procedure for Glaucoma.…”
Section: Introductionmentioning
confidence: 99%
“…An intraoperative complication rate of MSICS in HMCs was 14.3% in our study, which is marginally better than the 16% reported in ECCE. 20 However, Vajpayee et al in his study, on “Phacoemulsification in hypermature cataract,” evaluated the visual outcome in 25 patients and reported a nil complication rate. Nevertheless, it is important to note that all patients included in this study did not have any preoperative risk factors.…”
Section: Discussionmentioning
confidence: 99%